An Assessment of Electronic Medical Record Adoption in the Emergency Unit Using HOT-FIT Model: Evidence from RSUD A.M Parikesit - Lidia Putri Fitriana; Wahyu Wijaya Widiyanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The implementation of Electronic Medical Records (EMRs) in hospital emergency units is essential to improve the speed, accuracy, and quality of services. However, various challenges hinder optimal system utilization. This study aimed to assess the adoption of EMR at the Emergency Unit of RSUD A.M Parikesit Tenggarong using the Human-Organization-Technology Fit (HOT-FIT) framework. A qualitative descriptive approach was employed involving seven purposively selected informants, including health professionals, administrative staff, and IT personnel. Data were collected through interviews, observations, and document reviews, then analyzed using the Miles and Huberman interactive model. The findings indicate that from the human aspect, the system was considered easy to use (85%), though user satisfaction remained moderate (67.14%) due to system errors and incomplete CPPT data entries. Organizationally, the hospital provided adequate infrastructure and support, though some policies require stronger enforcement. Technological aspects revealed limitations in system stability, lack of pharmacy integration, and low service quality due to frequent downtime. The study concludes that EMR implementation in the Emergency Unit has not yet achieved full effectiveness across all HOT-FIT domains. Improvements are needed in system reliability, information consistency, and inter-unit integration to optimize EMR benefits and enhance patient care delivery in critical settings.